ENGLISH (CIPEEX, 2024)
THE ESTOCAQUI PROJECT REPRESENTS A COMPREHENSIVE AND INNOVATIVE SOLUTION AIMED AT REVOLUTIONIZING THE CONTROL OF PRODUCT ENTRY AND EXIT IN COMMERCIAL ESTABLISHMENTS, WITH A FOCUS ON RETAIL STORES. THE MAIN OBJECTIVE OF THIS SYSTEM IS TO ADDRESS THE SIGNIFICANT CHALLENGES FACED BY THIS SECTOR, FOCUSING ON OPTIMIZING INVENTORY CONTROL AND IMPROVING EFFICIENCY IN PRODUCT MANAGEMENT
Keywords: Inventory control; Product management; Data analysis; Operational efficiency.